SlCESTA Is a Brassinosteroid-Regulated bHLH Transcription Factor of Tomato That Promotes Chilling Tolerance and Fruit Growth When Over-Expressed - Shuai, Haiwei; Chen, Tingting; Wlk, Tanja; Rozhon, Wilfried; Pimenta Lange, Maria J.; Sieberer, Tobias; Lange, Theo; Poppenberger, Brigitte (Frontiers in Plant Science, 2022)
Brassinosteroids (BRs) are required for various aspects of plant growth and development, but also participate in stress responses. The hormones convey their activity through transcriptional regulation and posttranslational modification of transcription factors and one class are basic helix-loop-helix (bHLH) proteins of the BR Enhanced Expression (BEE) subfamily, which in Arabidopsis thaliana include BEE1-3 and CESTA (CES). CES and the BEEs promote the expression of different BR-responsive genes, including genes encoding gibberellin (GA) biosynthetic and catabolizing enzymes, as well as cold-responsive genes. Interestingly, in terms of an application, CES could promote both fruit growth and cold stress tolerance when over-expressed in A. thaliana and here it was investigated, if this function is conserved in the fruit crop Solanum lycopersicum (cultivated tomato). Based on amino acid sequence similarity and the presence of regulatory motifs, a CES orthologue of S. lycopersicum, SlCES, was identified and the effects of its over-expression were analysed in tomato. This showed that SlCES, like AtCES, was re-localized to nuclear bodies in response to BR signalling activation and that it effected GA homeostasis, with related phenotypes, when over-expressed. In addition, over-expression lines showed an increased chilling tolerance and had altered fruit characteristics. The possibilities and potential limitations of a gain of SlCES function as a breeding strategy for tomato are discussed.